Attracting Foreign Investments - The Basis Of National Economic Development - Nurdullaev Alisher Niyatilla ugli (Zien Journals, 2026)
This article analyzes the role and importance of attracting foreign investment in national economic development from a scientific and practical perspective. In the context of globalization, foreign investment not only brings additional financial resources to the country's economy, but also serves as an important factor providing access to modern technologies, advanced management experience, and opportunities for entering international markets. The article discusses the development of the real sector of the economy, modernization of industrial sectors, expansion of production of high value-added products, and creation of new jobs through the attraction of foreign investment. It also substantiates the importance of creating a favorable investment climate, improving legal guarantees, and institutional mechanisms for attracting foreign investment. The analysis reveals the role of foreign investment in increasing the competitiveness of the national economy, expanding export potential, and ensuring sustainable economic growth. The results of the article are of practical importance in further improving state policy aimed at attracting foreign investment
Keywords: foreign investment; direct investment; national economy